A Randomized Controlled Trial of an Automated Exercise Coach for Older Adults. Issue 10 (3rd September 2013) - Bickmore, Timothy W.; Silliman, Rebecca A.; Nelson, Kerrie; Cheng, Debbie M.; Winter, Michael; Henault, Lori; Paasche‐Orlow, Michael K.
<x xml:space="preserve">Abstract</x> Objectives To compare the efficacy of a computer‐based physical activity program (Embodied Conversational Agent—ECA) with that of a pedometer control condition in sedentary older adults. Design Single‐blind block‐randomized controlled trial stratified according to clinic site and health literacy status. Setting Three urban ambulatory care practices at Boston Medical Center between April 2009 and September 2011. Participants Older adults (N = 263; mean age 71.3; 61% female; 63% African American; 51% high school diploma or less). Intervention ECA participants were provided with portable tablet computers with touch screens to use for 2 months and were directed to connect their pedometers to the computer using a data cable and interact with a computer‐animated virtual exercise coach daily to discuss walking and to set walking goals. Intervention participants were then given the opportunity to interact with the ECA in a kiosk in their clinic waiting room for the following 10 months. Control participants were given a control pedometer intervention that only tracked step counts for an equivalent period of time. Intervention participants were also provided with pedometers. Measurements The primary outcome was average daily step count for the 30 days before the 12‐month interview. Secondary outcomes were average daily step count for the 30 days before the 2‐month interview. Outcomes were also stratified according to health literacy level. Results ECA participants walked significantly more steps than control participants at 2 months (adjusted mean 4, 041 vs 3, 499 steps/day, P = .01), but this effect waned by 12 months (3, 861 vs 3, 383, P = .09). For participants with adequate health literacy, those in the ECA group walked significantly more than controls at both 2 months (P = .03) and 12 months (P = .02), while those with inadequate health literacy failed to show significant differences between treatment groups at either time point. Intervention participants were highly satisfied with the program. Conclusion An automated exercise promotion system deployed from outpatient clinics increased walking among older adults over the short‐term. Effective methods for long‐term maintenance of behavior change are needed.